PERTIMBANGAN HAKIM TENTANG CERAI GUGAT SEORANG ISTRI DALAM KEADAAN HAMIL(STUDI KASUS PENGADILAN AGAMA KABUPATEN MALANG) - Mukhanad Khabib Mustofa; Ahmad Subekti; Dwi Ari Kurniawati (Jurnal Hikmatina, 2021)
In the case of divorce, a wife who is pregnant is in a religious court case. And this problem often feels strange in society. This case will be examined by researchers at the Religious Court of Malang Regency. This type of research uses qualitative. The researcher also uses judge interviews to add validity to this case. Thus, this study results that a wife's divorce in a pregnant state is allowed. The results of the judge's interview are khulu'. There is also a verse from the Qur'an in verse At-Talak verse 4 which means: "And women who are pregnant, their iddah is until they give birth to their womb". It is clear that if there is a period of iddah then divorce during pregnancy occurs and is allowed.